2017
DOI: 10.14740/jocmr2815w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-3 Polyunsaturated Fatty Acids on Dementia

Abstract: N-3 polyunsaturated fatty acids (PUFAs) including α-linolenic acid (ALA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have anti-inflammatory effects and neuronal protective functions and may benefit prevention of dementia; however, the epidemiological evidence is very limited. Therefore, the literature about the association between n-3 PUFA and dementia was searched, by using Pubmed. In the analyses of observational studies, n-3 PUFA has been reported to be beneficially associated with dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…Therefore, appropriate supplementation of EPA or DHA can improve cognitive impairment in elderly individuals [37]. Long-term dietary intake of α-linolenic acid (ALA) can improve the ability of learning and memory by regulating fatty acid content in the brain of patients with mild memory or cognitive impairment [38]. However, excessive proportions of n-6/n-3 fatty acids in the diet can cause mental retardation and brain damage like in Alzheimer's disease [39], and the decreased ratio of the n-6/n-3 fatty acid can help to regulate brain innate immune system activity, resist LPS-induced proinflammatory cytokine production and subsequent spatial memory changes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, appropriate supplementation of EPA or DHA can improve cognitive impairment in elderly individuals [37]. Long-term dietary intake of α-linolenic acid (ALA) can improve the ability of learning and memory by regulating fatty acid content in the brain of patients with mild memory or cognitive impairment [38]. However, excessive proportions of n-6/n-3 fatty acids in the diet can cause mental retardation and brain damage like in Alzheimer's disease [39], and the decreased ratio of the n-6/n-3 fatty acid can help to regulate brain innate immune system activity, resist LPS-induced proinflammatory cytokine production and subsequent spatial memory changes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Omega -3 fatty acids like α-linolenic acid, eicosapentaenoic acid, and docosahexaenoic acid have anti-inflammatory effects and neuroprotective actions which may be beneficial to AD. 32 Current study evaluated the neuroprotective potential of dietary oils like VCO and SO-enriched through diet in alleviating cognitive dysfunction induced by i.c.v administration of colchicine. The gas chromatographic analysis showed that VCO contains 54.48% of medium chain fatty acids (C6-C12).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrates a significant association of ALA with dementia. Serum ALA level is inversely associated with risk of disabling dementia (Devassy, Leng, Gabbs, Monirujjaman, & Aukema, ; Yanai, ). AA is important in learning and memory and can increase neuronal firing in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%